Methods Applied to the In Vitro Primary Toxicology Testing of Natural Products: State of the Art, Strengths, and Limits - Bunel, Valérian; Ouedraogo, Moustapha; Nguyen, Anh Tho; Stévigny, Caroline; Duez, Pierre (Planta Medica, 2014)
The present review attempts to build up a comprehensive picture of the major primary techniques used to screen and assess the cytotoxicity of plant complex mixtures. These can be based on metabolic activity, on membrane integrity, on morphological features, on cell growth; the type of cell death can also be established from more or less specific events (e.g., apoptosis, autophagy, DNA damage detection, reactive oxygen species involvement). This review will discuss the benefits, the difficulties, and the challenges that may occur along cytotoxicity testing of raw extracts and isolated natural compounds.
Keywords: biological assays; cytotoxicity; guidelines; pitfalls; natural products; toxicity screening